Does grass-legume intercropping change soil quality and grain yield in integrated crop-livestock systems? - Silva, Laércio Santos; Laroca, Jackeline Vieira dos Santos; Coelho, Anderson Prates [UNESP]; Gonçalves, Evelyn Custódio; Gomes, Romário Pimenta [UNESP]; Pacheco, Leandro Pereira; Carvalho, Paulo César de Faccio; Pires, Gabriela Castro; Oliveira, Rafael Loverde; Souza, Juliana Mendes Andrade de; Freitas, Caio Moretti; Cabral, Carlos Eduardo Avelino; et al. (Elsevier, 2022)
In sustainable tropical agriculture, grass-legume intercropping can increase productivity, enhance the nutritional quality of the crop and affect soil microbiological activity, leading to higher yields in succession crops. This study evaluated the impact of grass-legume intercropping, during the pasture phase of integrated crop-livestock systems under no-tillage (ICLS–NT), on soil microbiota, pasture quality, and soybean productivity in the Brazilian Cerrado. We evaluated the effect of intercropping on total soil contents of organic carbon and nitrogen, soil microbial activity, animal and soybean productivity (2017 and 2018 crop seasons), and pasture production and quality. The experiment consisted of twelve treatments under grass-legume intercropping in the pasture phase of ICLS–NT. The grasses Urochloa ruziziensis ‘Kennedy’, U. brizantha ‘Paiaguás’, Panicum maximum ‘Tamani’ and U. brizantha ‘Piatã’ were grown in monoculture and intercropped with cowpea (Vigna unguiculata) ‘Tumucumaque’ or pigeon pea (Cajanus cajan) ‘Mandarin’. A randomized block design, with three repetitions, was used in a split-plot arrangement, considering the grasses as plots and the legumes as subplots. The results showed that ICLS–NT improved the activity of soil microbial biomass when compared to monoculture systems. Grass-legume intercropping during the pasture phase, mainly with cowpea (Vigna unguiculata), increased soybean productivity, and grass dry matter. Total organic carbon (TOC), carbon management index (CMI%), microbial biomass carbon (MBC), soil basal respiration (BR), and metabolic quotient (Qmic) are the most sensitive markers when it comes to the effects of intercropping on soil microbiological activity and soybean productivity in ICLS–NT. Identifying the best grass-legume combinations allows the establishment of more productive crop-livestock integration systems under no-tillage better adapted to the bio-edaphoclimatic conditions of the Brazilian Cerrado.
Keywords: Crude protein; Grain yield; Soil microbiology; Soil organic carbon; Soybean